Hybrid Moral Sovereignty in Indonesia: Religion, Content Moderation, and Digital Public Authority - Abdul Wahid Hasyim (Pen Of Political Authority and Religion, 2026)
Digital platforms have become decisive arenas for the governance of public morality in Indonesia, where legal authority, religious legitimacy, and private moderation systems increasingly intersect. In this environment, disputes over visibility, prohibition, and reputational sanction are not merely technical matters of content control but contests over who may define legitimate public order. This article examines how hybrid moral sovereignty is produced through the interaction of state signaling, platform enforcement, religious authority, and digitally mobilized public pressure in Indonesia. The article adopts a qualitative, theory-driven approach grounded in political sociology, platform governance, and scholarship on religion and public authority. It draws on academic literature, policy and legal materials, platform-related public documents, media coverage, and publicly accessible cases of digitally mediated moral controversy in Indonesia. Analytical attention is directed to legal signaling, religious legitimacy, complaint infrastructures, and platform enforcement as interconnected mechanisms of norm production. A mechanism-based synthesis is used to explain how these actors co-produce binding moderation outcomes without a single sovereign center. Digital governance in Indonesia emerges as a hybrid regime in which state institutions, religious actors, platforms, and mobilized publics jointly shape enforceable moral order. The article concludes that content moderation in Indonesia is best understood as a field of distributed sovereignty in which public power is assembled through legal, moral, and infrastructural coordination. The article contributes to the field by offering a conceptually integrated framework for understanding how religion shapes political authority and how digital governance reconfigures sovereignty in a democratic but morally contested public sphere.